ECOLOGICAL CONCERNS OF AMITAV GHOSH WITH SPECIAL REFERENCE TO HIS NOVELS THE HUNGRY TIDE AND GUN ISLAND. - 1. Maalya S Jayan , 2. Dr. T. Mangayarkarasi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The phenomenon of ecological crisis is receiving the attention of people in the entire world. This article aims to demonstrate the deteriorating ecosystem and its effects on human and non-human world, with reference to the novels The Hungry Tide and Gun Island by Amitav Ghosh. It decodes the ecological crises in the Sundarban island and the way Ghosh indicated these issues in his novels. Human centric cultural practices contribute to the environmental crisis by giving people the power to control nature and triumph over it.